2014
DOI: 10.1007/s11606-014-2817-x
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Centered Interprofessional Collaborative Care: Factors Associated with Bedside Interprofessional Rounds

Abstract: These findings highlight factors associated with increasing or decreasing occurrence and time spent in bedside interprofessional collaborative care delivery. Systematic changes to census size caps, resident scheduling, and attending physician education and staffing may be required to increase the occurrence of interprofessional collaborative care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
54
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 31 publications
0
54
0
1
Order By: Relevance
“…29,39,40 Lastly, patients' ability to obtain, process, and understand information to improve their care, or health literacy, is a cross-cutting priority area in health policy. Studies demonstrate that patients have poor understanding of medical information presented to them, resulting in unnecessary admissions and emergency department utilization.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…29,39,40 Lastly, patients' ability to obtain, process, and understand information to improve their care, or health literacy, is a cross-cutting priority area in health policy. Studies demonstrate that patients have poor understanding of medical information presented to them, resulting in unnecessary admissions and emergency department utilization.…”
Section: Discussionmentioning
confidence: 99%
“…Two primary methods for team meetings in medicine units are care coordination rounds and team bedside interprofessional rounds, the latter of which are infrequent. 29,49 Additionally, team bedside rounds occur commonly during initial hospitalization days, rather than focusing on discharge transitions. 29,50 Standardization and utility of these two interprofessional team meetings may improve communication during patient discharges.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We were encouraged by the growing number of studies on interprofessional education, reflecting the national shift towards collaborative patientcentered medical homes and related care structures, but found little evidence regarding the impact on patient outcomes. 14,16,19,25 We also found descriptive studies on use of the milestone-based learner assessments. 18 Our selection process prioritized those most relevant, important, and generalizable, and with greatest methodological quality, for our audience of general internist educators.…”
Section: Discussionmentioning
confidence: 95%
“…[13][14][15][16][17][18][19][20][21][22][23][24][25] Compared to our review of the 2013 literature relevant to general medicine educators, 26 we found more multi-institutional studies of high quality. Similar to last year, resident continuity clinic and handoffs were areas of focus.…”
Section: Discussionmentioning
confidence: 99%